Virucidal activity of human α- and β-defensins against hepatitis C virus genotype 4. Issue 9 (21st June 2016) - Mattar, Ehab H.; Almehdar, Hussein A.; Uversky, Vladimir N.; Redwan, Elrashdy M.
Abstract : We revealed that human α- and β-defensins have strong anti-HCV activity in experiments on cellular protection, neutralization, and treatment at low concentrations, whereas synthetic linear avian defensins could reach similar anti-HCV potential only at noticeably higher concentrations. Abstract : Hepatitis C virus (HCV) is the major etiological agent of human non-A and non-B hepatitis affecting about 180 million people worldwide. The goal of the current study was to find effective anti-HCV proteins. As a result, defensins were selected as promising candidates due to their well-known anti-viral potential and small size. We conducted in vitro evaluation of two kinds of defensins (human α- and β-defensins and synthetic linear avian α-defensins) using tissue culture combined with reverse transcription nested PCR (RT-nested-PCR) and real-time PCR. Human α- and β-defensins showed strong anti-HCV activity in experiments on cellular protection, neutralization, and treatment at all concentrations used (10, 20 and 50 μg). The synthetic linear defensins could reach similar anti-HCV potential only at a noticeably higher concentration (250 μg) and do not show noticeable activity at 10 and 20 μg. This study suggests that defensins are potent anti-HCV agents.